CONTENT ANALYSIS OF TIKTOK IN SHAPING PUBLIC OPINION ON THE CASE OF A STUDENT BEING SLAPPED AT SMA NEGERI 1 CIMARGA - Assuhaila, Nabila; Hidayat, Rahmat (International Journal of Cultural and Social Science, 2026)
The virality of school violence cases on social media not only accelerates the spread of information but also creates a new arena for the production, circulation, and legitimacy of public opinion. However, studies on how TikTok frames cases of school violence and how netizen interactions reproduce moral judgments about disciplinary actions are still relatively limited, particularly in cases involving educational authority figures. This study aims to analyze the form of TikTok content discussing the case of a student being slapped at SMA Negeri 1 Cimarga and identify trends in public opinion emerging through the comments section. The study used a descriptive qualitative approach with a content analysis method on 30 TikTok posts and 250 comments purposively selected based on issue relevance and level of interaction. The results show that the content and comments are dominated by narratives supporting the principal's actions by emphasizing the value of discipline, while others interpret them as a form of violence against students. These findings suggest that TikTok functions not only as a medium for information distribution but also as an arena for framing and amplifying opinions that can normalize problematic disciplinary actions through algorithmic logic and comment resonance. Academically, this research contributes to the development of digital communication studies, public opinion, and social media analysis by emphasizing that public opinion on TikTok is formed through the relationship between content narratives, user interactions, and social values ??that exist in society.